FapR: From Control of Membrane Lipid Homeostasis to a Biotechnological Tool - Albanesi, Daniela; de Mendoza, Diego (Frontiers in Molecular Biosciences, 2016)
Phospholipids and fatty acids are not only one of the major components of cell membranes but also important metabolic intermediates in bacteria. Since the fatty acid biosynthetic pathway is essential and energetically expensive, organisms have developed a diversity of homeostatic mechanisms to fine-tune the concentration of lipids at particular levels. FapR is the first global regulator of lipid synthesis discovered in bacteria and is largely conserved in Gram-positive organisms including important human pathogens such as Staphylococcus aureus, Bacillus anthracis, and Listeria monocytogenes. FapR is a transcription factor that negatively controls the expression of several genes of the fatty acid and phospholipid biosynthesis and was first identified in Bacillus subtilis. This review focuses on the genetic, biochemical and structural advances that led to a detailed understanding of lipid homeostasis control by FapR providing unique opportunities to learn how Gram-positive bacteria monitor the status of fatty acid biosynthesis and adjust the lipid synthesis accordingly. Furthermore, we also cover the potential of the FapR system as a target for new drugs against Gram-positive bacteria as well as its recent biotechnological applications in diverse organisms.